Effect of Solvent on PL Spectra for Defect Analysis of CuO Nanoparticles (Chemical Engineering Research Bulletin, 2023)
Copper oxide (CuO) is one of the potential semiconductor metal oxides which has numerous possible applications in optoelectronic device applications. Nanoparticles (NPs) for such applications require high end optical characterization, for which photoluminescence (PL) spectroscopy is considered as one of the most important tools to reveal the optical and electronic band structures along with defects. The electron hole recombination rate and the defect structures are important criteria determining the performance of nanoparticles in such applications, i.e., photocatalytic degradation of dyes and to get insights into these parameters can help to explain the mechanism of photocatalytic degradation. One of the convenient ways to conduct PL spectroscopy of such nanoparticles is by dispersing in liquid solvent. However, due to solute-solvent interaction, characterization and analysis of PL spectra can be quite challenging sometimes as the PL intensity shows variation for the same NPs but dispersed in different solvents. In this study, CuO NPs were synthesized by co-precipitation method, characterized using x-ray diffraction (XRD), field emission scanning electron microscopy (FE SEM), ultra-violet visible spectroscopy (UV-Vis) and photoluminescence spectroscopy. Three different solvents were used for PL, which includes methanol, ethanol, and isopropanol. Finally, the effect of these solvents on PL spectra of the NPs was studied thoroughly.Chemical Engineering Research Bulletin 23 (2023): 108-112